Analisis Pengaruh Perceived Easy of Use, Religiosity, dan Perceived Usefulness terhadap Minat Berdonasi Online Melalui Trust - Irman Nasrudin; Hanny Nurlatifah; Shohibul Imam (Neolectura, 2023)
The purpose of this study was to determine the effect of the analysis of Perceived Easy of use, Religosity, and Perceived usefulness of Trust on online donation intentions. This study uses a quantitative approach with the number of samples taken using the Non-Probability Sampling technique by means of Purposive sampling as many as 100 respondents for this study. The data analysis method used is descriptive analysis and path analysis. The sample used in this study were respondents aged 20-40 years, active in South Jakarta and have made online donations in the last 12 month in an institutions. Based on the research that has been done, the conclusions that can be drawn are that the variables Perceived Easy of use, Religiosity and Perceived Usefulness through Trust on online donation interest have a positive effect, meaning that there is a direct and significant relationship to online donation interest.